Laser nephelometry applied in an automated microplate system to study filamentous fungus growth. (May 2010) - Joubert, Aymeric; Calmes, Benoît; Berruyer, Romain; Pihet, Marc; Bouchara, Jean-Philippe; Simoneau, Philippe; Guillemette, Thomas
By contrast with photometry (i.e., the measurement of light transmitted through a particle suspension), nephelometry is a direct method of measuring light scattered by particles in suspension. Since the scattered light intensity is directly proportional to the suspended particle concentration, nephelometry is a promising method for recording microbial growth and especially for studying filamentous fungi, which cannot be efficiently investigated through spectrophotometric assays. We describe herein for the first time a filamentous fungi–tailored procedure based on microscale liquid cultivation and automated nephelometric recording of growth, followed by extraction of relevant variables (lag time and growth rate) from the obtained growth curves. This microplate reader technique is applicable for the evaluation of antifungal activity and for large-scale phenotypic profiling.